Contribuição a previsão de vida útil de estruturas de concreto armado sujeitas à corrosão por transporte de cloretos: uma abordagem ao fluxo convectivo de íons cloreto - Suzano, Ana Beatriz Pimenta (2017)
Concrete, as a building material, is unstable over time and its alterations compromise the performance of a structure. Reinforcement corrosion is one of the major problems facing reinforced concrete structures because of the substantial reduction of the steel area, loss of adhesion, cracking and spalling of concrete, and the main cause is the attack of chlorides. Over the last decades, several researches have been carried out to predict the service life of reinforced concrete structures subjected to the attack of chlorides. With these surveys, a variety of models have emerged to assist engineers. This work presents a contribution to the prediction of service life of reinforced concrete structures. Some predictive models with analytical or numerical solution are analyzed and a numerical model are developed using the finite element method based on the aspects that were analyzed from other models. The numerical model developed in this study takes into account the environmental fluctuations of humidity and temperature, chlorides binding, diffusion and convection. Drying and wetting cycles are also covered. Three coupled equations are solved: heat transfer, moisture flow and chloride transport. The model is applied to a beam in a marine region in the city of Vitória, ES and the results are compared with the analytic solution and the model proposed by Dominicini (2016). In addition, other simulations involving convection, chloride bonding and wetting and drying cycles are performed.